2020
DOI: 10.3390/ijerph17238714
|View full text |Cite
|
Sign up to set email alerts
|

Do Initial Trunk Impairment, Age, Intervention Onset, and Training Volume Modulate the Effectiveness of Additional Trunk Exercise Programs after Stroke? A Systematic Review with Meta-Analyses

Abstract: The aim of this systematic review is to analyze how, after additional trunk-focused training programs (ATEP), motor recovery after a stroke is modulated by potential effect modifiers. Twenty randomized controlled studies that carried out ATEP were included. Results showed moderate-to-high effects in favor of ATEP for trunk function, balance ability, gait performance, and functional mobility. Studies with a higher initial trunk impairment obtained a higher effect on trunk function and balance; studies with olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Furthermore, responders displayed lower balance ability, both in static and dynamic balance ability preintervention. This is in line with previous results that show initial impairment to influence outcomes after rehabilitation [ 13 , 15 , 18 ]. Moreover, Schwenk et al [ 19 ] demonstrated that lower baseline balance performance was associated with a greater improvement in balance outcomes after VR therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, responders displayed lower balance ability, both in static and dynamic balance ability preintervention. This is in line with previous results that show initial impairment to influence outcomes after rehabilitation [ 13 , 15 , 18 ]. Moreover, Schwenk et al [ 19 ] demonstrated that lower baseline balance performance was associated with a greater improvement in balance outcomes after VR therapy.…”
Section: Discussionsupporting
confidence: 93%
“…Prat-Luri et al [ 18 ] identified through meta-analysis various effect modifiers that influence the effectiveness of trunk training programs. Studies that included participants with higher initial trunk impairment resulted in a higher impact of treatment on trunk function and balance ability.…”
Section: Introductionmentioning
confidence: 99%
“…The choice to include both frontal and lateral movements is because stroke survivors commonly manifest more difficulty in lateral movements ( 47 , 48 ): we, therefore, expected to detect differences in the execution, control, and coordination of movements in the two proposed directions. In addition, several studies have shown that simultaneous movements stimulate the reactivation of areas in the partially damaged hemisphere, leading to improved paretic limb functions ( 49 ).…”
Section: Methodsmentioning
confidence: 99%
“…Trunk exercises, such as those that challenge trunk stability (i.e., the capability to maintain or resume a relative position or trajectory of the trunk following internal or external forces 1 ) or trunk muscle endurance (i.e., the capability to exert trunk muscle force continuously over the long periods of time 2 ), have become common elements of training programs to improve whole‐body balance (i.e., the capability to maintain the center of mass within the body's base when performing a standing movement in order to perform multiple actions safely and accurately 3 ) in a wide range of populations, such as athletes, 4 sedentary people, 4 stroke patients, 5 and older adults 6 . In this sense, as the upper body is usually far from the ground and accounts for approximately two‐thirds of the total body weight, 7 trunk muscle function seems to play a relevant role in actions that require large dynamic balance demands so even small uncoordinated trunk movements may hamper body control 8 .…”
Section: Introductionmentioning
confidence: 99%